Optimal Policy with R&D-based Growth and the Risk of Environmental Disaster - Tapio Palokangas (Helsinki Graduate School of Economics, 2023)
The extraction of carbon energy contributes to the global stock of pollution, increasing the risk of welfare-damaging environmental dis- aster. The governments of the countries educate workers as scientists. Oligopolists produce goods by workers and carbon energy. R&D firms improve efficiency by scientists to supplant incumbent oligopolists through competition, which generates economic growth. In this setup, an international central planner can decentralize the social optimum by setting a precautionary tax on emissions before the occurrence of the disaster. That tax hampers pollution, but speeds up economic growth. The socially optimal level of the tax is derived.
Keywords: H21; O32; O44; Q54; Q58; 330; emissions; pollution; R&D; endogenous growth; environmental disaster; precautionary policy